Occurences of endophytic fungi in Musa acuminata - Elmy Fazriena, binti Md Yusof (Universiti Malaysia Sarawak (UNIMAS), 2015)
Endophytic fungi are microorganisms that live within a plant tissue and have been found almost in all plant species without causing any symptoms in their hosts. Endophytic fungi were isolated from fruits, leaves, pseudostems and petioles of cultivar Kapas and cultivar Tanduk. A total of 16 species of endophytic fungi were found during this study. They were Aspergillus flavus, A.niger, Botryodiplodia theobromae, Colletotrichum musae, Cordana musae, Fusarium sp., Geotrichum sp., Guignardia sp., Nigrospora sp. and Penicillium sp. The most common endophytic fungi found was A.niger. Morphological and physiological characteristics of the endophytic fungi were also studied. The effects of various temperature, light and pH on selected fungi were examined. ANOVA analysis showed that each test had significant different to the fungi growth. The optimum temperature ranges for growth of selected endophytic fungi were between 20°C to 30°C. The light conditions had significant effect on selected endophytic fungi growth. The optimum pH for each selected endophytic fungi species differ from each other.